2023
DOI: 10.3390/antiox12040975
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia Synaptic Pathology and Antipsychotic Treatment in the Framework of Oxidative and Mitochondrial Dysfunction: Translational Highlights for the Clinics and Treatment

Abstract: Schizophrenia is a worldwide mental illness characterized by alterations at dopaminergic and glutamatergic synapses resulting in global dysconnectivity within and between brain networks. Impairments in inflammatory processes, mitochondrial functions, energy expenditure, and oxidative stress have been extensively associated with schizophrenia pathophysiology. Antipsychotics, the mainstay of schizophrenia pharmacological treatment and all sharing the common feature of dopamine D2 receptor occupancy, may affect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 332 publications
(493 reference statements)
0
2
0
Order By: Relevance
“…F2-isoprostanes are ROS-mediated products of arachidonic acids and are very sensitive markers of the lipid peroxidation process (Dietrich-Muszalska and Kontek 2010 ). Increased levels of isoprostanes, and predominantly 8-iso-prostaglandin (8-iso-PGF2α) have been detected in the urine of patients, making analysis of isoprostanes a valuable and reliable marker of the level of oxidative damage in schizophrenia patients (De Simone et al 2023 ).…”
Section: Oxidative Stress Diseases Aging and Antioxidant Interventionsmentioning
confidence: 99%
“…F2-isoprostanes are ROS-mediated products of arachidonic acids and are very sensitive markers of the lipid peroxidation process (Dietrich-Muszalska and Kontek 2010 ). Increased levels of isoprostanes, and predominantly 8-iso-prostaglandin (8-iso-PGF2α) have been detected in the urine of patients, making analysis of isoprostanes a valuable and reliable marker of the level of oxidative damage in schizophrenia patients (De Simone et al 2023 ).…”
Section: Oxidative Stress Diseases Aging and Antioxidant Interventionsmentioning
confidence: 99%
“…On the one hand, it has been shown that subjects with schizophrenia experience endogenous oxidative stress, which can trigger the initiation of symptoms [8]. On the other hand, antipsychotic treatment may trigger oxidative imbalance; however, both typical and atypical antipsychotics vary significantly in their effects on redox balance [36].…”
Section: Discussionmentioning
confidence: 99%
“…Regulating GABA A R desensitization is an essential process that is controlled at the signaling pathway and receptor levels; however, modulating receptor function at the level of the energy processes plays a key role in understanding withdrawal in neurological and psychiatric disorders ( Rezin et al, 2009 ). Mitochondrial dysfunction is a key factor in epilepsy, Parkinson’s disorder, schizophrenia, and other synaptic and extra-synaptic pathologies ( De Simone et al, 2023 ). However, the relationship between GABA A R activity, impaired energy balance, and manifestations of NPDs remains poorly understood.…”
Section: Molecular Mechanisms Underlying the Action Of Phenols On Gab...mentioning
confidence: 99%